Cancer Theranostics: A Novel Top‐Down Synthesis of Ultrathin 2D Boron Nanosheets for Multimodal Imaging‐Guided Cancer Therapy (Adv. Mater. 36/2018). Issue 36 (3rd September 2018) - Ji, Xiaoyuan; Kong, Na; Wang, Junqing; Li, Wenliang; Xiao, Yuling; Gan, Silvia Tian; Zhang, Ye; Li, Yujing; Song, Xiangrong; Xiong, Qingqing; Shi, Sanjun; Li, Zhongjun; et al.
Abstract : In article number1803031, Han Zhang, Lin Mei, Jinjun Shi, and co‐workers demonstrate a method of top‐down synthesis of 2D boron nanosheets through coupling thermal oxidation etching and liquid‐exfoliation technologies. Based on PEGylated boron nanosheets, a new photonic drug‐delivery platform is developed for multimodal‐imaging‐guided (fluorescence, photoacoustic, and photothermal imaging) cancer therapy (photothermal therapy and chemotherapy).